Development and characterization of sitagliptin smart film tablets - S. Sanjeev; C. Santhosh kumar (International Journal of Pharmacy and Analytical Research, 2022)
The possibility to compress ordinary paper into tablets was systematically investigated in this study. The model drug Sitagliptin loaded in to the paper and studied various tableting characters. The drug-loaded tablets were produced by direct compression method without using and additives. Results proved that tablets can be made from paper, independent of the type of paper used. The tablets appear shiny and with a smooth surface. The pharmaceutical quality was acceptable, i.e. all tablets fulfilled the requirements for tablets according to the Indian Pharmacopeia. However, the uncoated tablets possessed fast disintegration, i.e. intense swelling upon contact with water. To tablets were successfully coated with a polymer film, leading to a delay the disintegration in simulated gastric fluid. In Post-compression characterization, coated and uncoated, drug content was found to be in the range of 95 to 99% with round shape and having hardness of 2.15-5 kg/cm2. Percent weight variation was observed between 4.0 and 6.1 with friability of between 0.34 to 0.66%. The disintegration time of uncoated tablets prepared by direct compression were found to be in the range of 19-20 seconds and the coated tablet 6.2-12.1 min. The drug loaded tablet made by facial tissue paper (uncoated tablet F2 and coated tablet F7) showed highest time duration for disintegration. In fact, tablets made from paper are a novel and promising strategy for improved oral drug delivery. They can be easily produced without any further excipients and possess pharmaceutical quality according to the Indian pharmacopeia.